Studying extent of internet usage among student of universities located at İstanbul - Tan Cömert, Itır; Ziyalar, Neylan (Journal of Dependence, 2009)
Objective: This study has been conducted to examine the extent of internet usage among university students aged between 18-28 who reside in Istanbul, and are enrolled in undergraduate, post graduate and doctorate programs. Methods: The study encompasses university students aged between 18-28 who reside in Istanbul, and are enrolled in undergraduate, post graduate and doctorate programs in the year 2006. The study forms a part of the doctoral thesis. This study has been conducted upon obtaining the necessary approval dated 12-04-2006 and numbered 2006/392 from the Cerrahpasa Committee of Ethics. The sample size has been established as 600 students. The statistical calculations have been conducted using the SPSS 8,0 program. Results: 346 (%57.7) of the students who have participated in the study were female and 254 (%42.3) are male. 77% of the participants were aged between 18-22, 14.7% were between 23-25 and 8.3% were between 26-28. 77.8% of the sample have demonstrated to possess the criteria to be characterized as internet addicts. Conclusion: TThe internet is global source of information. The number of people who use the internet in their daily lives are increasing. Te problems arising from problematic internet usage must be tackled as a whole.